Comparison of High-sensitivity C-reactive Protein Level between Chronic Kidney Disease Stages - Mochammad Thaha; Tri Asih Imroati; Aditia Wardana; Widodo Widodo; Pranawa Pranawa; chandra irwanadi (Biomolecular and Health Science Journal, 2018)
ABSTRACTAim : This research is to evaluate the hs-CRP level comparison between CKD stages in Dr. Soetomo General Hospital Surabaya.Methods: An analytic observational cross-sectional study, evaluating the differences of hs-CRP level between CKD stages in 72 patients (mean age 55.49±7.62 years, the ratio between male:female was 1:1.48, mean BMI 24.18±3.64 kg/m2, 36.11% diabetics, 43.05% on ACEI/ARB, 29.16% on statin), recruited from Nephrology Outpatient Clinic, Dr Soetomo General Hospital, Surabaya, from January to May 2014. The stages were stratified  according to the MDRD formula.Results: The mean hs-CRP of  CKD stage 3 was 2.29±2.86, stage 4 was 2.48 ± 2.19, and non-dialysis stage 5 was 2.09 ± 2.54. The analysis using Kruskal-Wallis test showed no significant differences among patients with  CKD stage 3, stage 4, and non-dialysis stage 5 (median 1.25 vs 1.80 vs 1.05 mg/L; p=0.430). No significant differences of the serum hs-CRP level were detected between diabetics and non diabetics in stage 3, 4, and non-dialysis stage 5  (p=0.673 vs 0.666 vs 0.138); between patients with and without ACEI/ARB treatment (p=0.610 vs 0.649 vs 0.671); and between patients with and without statin treatment (p=0.852 vs 0.341 vs 0.309).Conclusion: The elevation of serum hs-CRP level can not indicate the decline of kidney function, but it still needs further investigations.